2018
DOI: 10.1111/jdi.12795
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of resting energy expenditure and body composition in Japanese pregnant women with diabetes

Abstract: Aims/IntroductionTo measure longitudinal changes in resting energy expenditure and body composition of Japanese pregnant women with or without diabetes.Materials and MethodsThe study population consisted of women who had delivered a live singleton neonate after 22 weeks’ gestation at Okayama University Hospital from July 2013 to June 2017. Resting energy expenditure and body composition were measured in the first trimester, second trimester, third trimester and postpartum.ResultsA total of 144 women participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 32 publications
(33 reference statements)
0
16
0
Order By: Relevance
“…27 The magnitude of increase in energy requirements during pregnancy has been a matter of debate. 17 In clinical practice, TEE based on pre-pregnancy BMI is often used to guide the need for energy intake in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 The magnitude of increase in energy requirements during pregnancy has been a matter of debate. 17 In clinical practice, TEE based on pre-pregnancy BMI is often used to guide the need for energy intake in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…16 Therefore, REE could be a helpful monitoring tool to assess energy intake during pregnancy, especially for obese/overweight women. 17 Some investigators suggested that interventions could be developed to tailor recommendations for energy intake for women's needs based on REE measured in clinical setting. 18,19 We therefore tested the hypothesis that REE guided management of GWG for pregnant women with obesity/overweight may be helpful in a small-scale study.…”
Section: Reementioning
confidence: 99%
“…25 The magnitude of increase in energy requirements during pregnancy has been a matter of much debate. 10 In clinical practice, TEE based on to pre-pregnancy BMI is often used to guide the need for energy intake in pregnancy. Byrne et.al 26 suggested that TEE based on REE was more accurate than TEE based on pre-pregnant BMI.…”
Section: Discussionmentioning
confidence: 99%
“…9 Therefore, REE could be a helpful monitoring tool to assess energy intake during pregnancy, especially for obese/overweight women. 10 Some investigators thought that interventions could be developed to tailor recommendations for energy intake for women's needs based on REE measured in clinical setting. 11,12 Obesity and overweight have become a major public health problem worldwide.…”
Section: Reementioning
confidence: 99%
“…This study found unique changes in REE across the participants that were not consistent with predictive equations [19]. It is apparent that REE is a highly variable measure that is impacted by numerous biological (disease status) [20,21] and behavioral (activity level [9], nutrition [10], and sleep [22]) factors. Consideration of REE in conjunction with other biological and behavioral factors may improve dietary and GWG recommendations during a critical period of growth and development.…”
Section: Introductionmentioning
confidence: 94%